Yu-Gi-Oh! 5D's. Volume 7, Last draw of destiny! - Hikokubo, Masahiro (Viz Media, 2015)
As Goodwin's battle against Jack Atlas reaches its end, Crow Hogan releases the other duelists in order to help Yusei in his fight against the Skeleton Knight, but they may be too late.